Pengelolaan Rancangan Organisasi Umat Buddha di Padepokan Dhammadipa Arama Batu Jawa Timur - I Ketut Damana (STABN Sriwijaya, 2018)
The problem raised in this study is that he has not yet known Management in the design of the Buddhist organization in the Padepokan Dhammadipa Arama Batu East Java. The purpose of this article is to find out the design of the management Buddhist organizations in the Padepokan Dhammadipa Arama Batu East Java.This study included a type of discrete qualitative research, informants in this study were Buddhists in Padepokan Dhammadipa Arama, data collection techniques used were interviews, observation, and documentation, with instruments in the form of observation guidelines and interview guidelines. The data analysis technique uses the Miles and Hubermen models which consist of four stages, data collection, data reduction, data presentation and conclusion or verification.The results of this study are (a) Forms of Buddhist Organizational Design in the Padepokan Dhammadipa Arama in the form of training and collaboration aimed at obtaining debriefing, adding knowledge and more planned planning. (b) Factors that influence the Design of Buddhist Organizations in Padepokan Dhammadipa Arama Batu East Java. In the form of human resources and technology. The aim is to increase motivation in designing Buddhist organizations. (c) Strategies that influence the Design of Buddhist Organizations in the Padepokan Dhammadipa Arama East Java. The form of financial management and management of cooperatives is intended to develop the design of Buddhist organizations. (d) Constraints in implementing the Design of Buddhist Organizations in Padepokan Dhammadipa Arama is lack of time, lack of readiness and lack of supervision. (e) Response that affects the Draft Organization of Buddhists in Padepokan Dhammadipa Arama is there are satisfied and dissatisfied, the purpose of the response responded to by Buddhists by correcting bad behavior and adding more performance designs. Permasalahan yang diangkat dalam penelitian ini adalah belum diketahuinya pengelolaan dalam rancangan organisasi umat Buddha di Padepokan Dhammadipa Arama Batu Jawa Timur. Tujuan artikel ini untuk mengetahui pengelolaan rancangan organisasi umat Buddha di Padepokan Dhammadipa Arama Batu Jawa Timur.Penelitian ini termasuk jenis penelitian kualitatif deskriptif. Informan dalam penelitian ini adalah umat Buddha di Padepokan Dhammadipa Arama. Teknik pengumpulan data yang digunakan adalah dengan wawancara, observasi, serta dokumentasi, dengan instrumen berupa pedoman observasi dan pedoman wawancara. Teknik analisis data menggunakan model Miles Hubermen yang terdiri dari empat tahapan, yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi.Hasil penelitian ini adalah: (a) bentuk-bentuk rancangan organisasi umat Buddha di Padepokan Dhammadipa Arama berupa adanya pelatihan dan kerja sama tujuannya untuk memperoleh pembekalan, menambah pengetahuan dan perencanaan lebih terencana; (b) faktor-Faktor yang mempengaruhi rancangan organisasi umat Buddha di Padepokan Dhammadipa Arama Batu Jawa Timur, yaitu adanya sumber daya manusia dan teknologi yang bertujuan menambah motivasi dalam merancang organisasi umat Buddha; (c) strategi yang mempengaruhi rancangan organisasi umat Buddha di Padepokan Dhammadipa Arama Jawa Timur berupa pengelolaan keuangan dan koperasi yang tujuannya untuk berkembangnya rancangan organisasi umat Buddha; (d) kendala dalam pelaksanaan rancangan organisasi umat Buddha di Padepokan Dhammadipa Arama adalah kurang waktu, kurang siap, dan kurang pengawasan; (e) respons yang mempengaruhi rancangan organisasi umat Buddha di Padepokan Dhammadipa Arama adalah ada yang puas dan tidak puas, yang ditanggapi oleh umat Buddha dengan memperbaiki perilaku yang tidak baik dan menambah lagi rancangan kinerja.